Three new Oligaphorura species (Collembola: Onychiuridae) of the marcuzzii-group from the Caucasus - Shveenkova, Yulia B.; Babenko, Anatoly B. (Zootaxa, 2022)
Three new species of the genus Oligaphorura, namely O. montivaga sp. nov., O. tatianae sp. nov., and O. igori sp. nov., are described based on materials from different parts of the Caucasus. All of them belong to the marcuzzii-group of the genus because of the presence of 4+4 pso at the antennal base and the absence of anal spines. They seem to be especially similar to O. kremenitsai Shvejonkova & Potapov and O. humicola Shvejonkova & Potapov, two congeners with the same uncommon type of the labium (ABD), but are distinguished by the number of dorsal pseudocelli (42/144/33354 in O. kremenitsai, 42/133/33354 in O. humicola, 43/144/44354 in O. montivaga sp. nov., 43/133/44(5)364 in O. tatianae sp. nov. and 43/133/44354 in O. igori sp. nov.). Apart from this, all new species have the schoetti-type furcal area and more distal setae on the tibiotarsi (11 in O. montivaga sp. nov. and O. tatianae sp. nov. and 9 in O. igori sp. nov.) whereas both O. kremenitsai and O. humicola show the humicola-type furcal area and only 6 distal setae on the tibiotarsi. A table with the main diagnostic features of Oligaphorura species of the marcuzzii-group is also given.